Correlation of Advance Sustainability Indexes and Consciousness of Life Prospects of Military Academy Cadets: medical-psychological aspects - Norchuk, Yurii; Miloradova, Natalia; Turban, Victoria; Matiash, Mykhailo; Slurdenko, Dmytro; Вeata, Barchi (International Journal of Psychosocial Rehabilitation, 2020)
The paper indicates results of empiric research of interrelationship between advance sustainability components and life prospects of personality. Phenomenon of advance sustainability of personality is considered in the context of determination and interconditionality of life-time prospects. Advance sustainability is viewed as functional-energy organ - personality creation, presented by specific functionality of psychological boundaries of personality, anticipatory-preventive capacity, structure of intrapersonal conflicts, type of orientation on action, alienation, adaptation capacity, orientation on time context of life activity. Peculiarities of advance sustainability formation using an example of cadets of higher soldiery educational establishments of Ministry of Defense of Ukraine at the educational-academic stage of professional socialization have been defined.